The Problems of rendering psychological assistance to oncological patients in the region of Russian Federation - Igorevna, Leskina Eleonora (European Journal of Oncology and Environmental Health, 2018)
Among the most urgent problems of our time, oncological diseases occupy a special place. When the diagnosis sounds like a sentence, when people need highly qualified and expensive help, the state can not stay away. And one of the types of social security here is qualified medical psychological assistance. The aim of the article: Is to study various aspects of psychological care for cancer patients in the Saratov region. Methodological basis: The methods used are both empirical (analysis and synthesis, induction and deduction, systematization), and theoretical (methods of constructing and researching the object of research and methods of constructing and justifying theoretical knowledge) levels. Results: The dynamics and prevalence of people who need psychological help in connection with the diagnosis of cancer is shown. The article considers the history of medical care for cancer patients in the Saratov region, the main forms of providing psychological assistance to cancer-patients in the region. Conclusions: Currently, there is a shortage of cancer-psychologists in the region, it is necessary to provide psychological support for cancer -psychologists to persons who underwent preventive operations in connection with the high probability of hereditary cancer within the framework of MHI. Among the most urgent problems of our time, oncological diseases occupy a special place. When the diagnosis sounds like a sentence, when people need highly qualified and expensive help, the state can not stay away. And one of the types of social security here is qualified medical psychological assistance. The aim of the article: Is to study various aspects of psychological care for cancer patients in the Saratov region. Methodological basis: The methods used are both empirical (analysis and synthesis, induction and deduction, systematization), and theoretical (methods of constructing and researching the object of research and methods of constructing and justifying theoretical knowledge) levels. Results: The dynamics and prevalence of people who need psychological help in connection with the diagnosis of cancer is shown. The article considers the history of medical care for cancer patients in the Saratov region, the main forms of providing psychological assistance to cancer-patients in the region. Conclusions: Currently, there is a shortage of cancer-psychologists in the region, it is necessary to provide psychological support for cancer -psychologists to persons who underwent preventive operations in connection with the high probability of hereditary cancer within the framework of MHI.